Adaptive self-reflection and resilience: The moderating effects of rumination on insight as a mediator. (February 2022) - Bucknell, K.J.; Kangas, M.; Crane, M.F.
Abstract: Self-focused attention literature identifies inconsistencies which suggest that self-reflection does not have a direct relationship with resilient outcomes. This study aimed to clarify the associated mechanisms by (1) exploring the indirect relationships between general and adaptive self-reflection and mental health outcomes via insight, and (2) testing the role of rumination as a moderator of this mediating relationship. Two-hundred and seventy-seven Australian Protestant ministry workers completed an online survey measuring adaptive self-reflection, general self-reflection, insight, rumination, resilience, and well-being. Structural equation modelling identified a moderated mediation. Insight mediated the relationship between adaptive self-reflection and resilience. Rumination moderated this relationship such that when ruminative thought was low, a positive relationship existed between adaptive self-reflection and resilience via insight. When rumination was high, adaptive self-reflection was negatively related to resilience via insight. Similar relationships were found between adaptive self-reflection and well-being, but not when general self-reflection was the independent variable. These results demonstrate one possible mechanism in the relationship between self-reflection and positive mental health, and the conditional role of rumination.